Longitudinal Trends in Sport Participation and Retention of Women and Girls - Eime, Rochelle; Harvey, Jack; Charity, Melanie; Westerbeek, Hans (Frontiers in Sports and Active Living, 2020)
Measurement and analysis of sport participation data is vital to understand trends, and therefore to make informed decisions relating to sport policy and strategies to get more people active through sport. This study identified patterns of club sport participation, retention and dropout of females over a 7-year period in a popular female team sport in Australia. This study included all registered female sport participants of all ages (4-96 years) in an almost female exclusive sport, and also included a particular focus on the ages 4-14 years where most participation occurs. All commencing participants in the base year (2010) were tracked over the 7-year period. Participants were classified in three ways: the total number of years they played, the number of consecutive years they played, and their overall pattern of participation. The number of years played, in total and consecutively, were compared across age groups, using Kruskall Wallis and Mann Whitney tests. A total of 30,096 participant records were analyzed. Overall, there were considerable differences in the years participating in the sport. Nearly 30% of 4-9 year olds (29.4%) played continuously for the 7 years. From ages 10-19 there was an increase in single year players. The optimal age of entry to sport for retention in participation is 6-9 years. Younger children should be directed towards the development of fundamental movement skill development programs rather than entering organised club-based sport. Strategies specifically relating to retention of female adolescents should be developed.